Diagnostic accuracy of physician's gestalt in suspected COVID‐19: Prospective bicentric study. (15th March 2021) - Nazerian, Peiman; Morello, Fulvio; Prota, Alessio; Betti, Laura; Lupia, Enrico; Apruzzese, Luc; Oddi, Matteo; Grosso, Federico; Grifoni, Stefano; Pivetta, Emanuele; ,
ABSTRACT: Objectives: Physicians' gestalt is central in the diagnostic pipeline of suspected COVID‐19, due to the absence of a single tool allowing conclusive rule in or rule out. The aim of this study was to estimate the diagnostic test characteristics of physician's gestalt for COVID‐19 in the emergency department (ED), based on clinical findings or on a combination of clinical findings and bedside imaging results. Methods: From April 1 to April 30, 2020, patients with suspected COVID‐19 were prospectively enrolled in two EDs. Physicians prospectively dichotomized patients in COVID‐19 likely or unlikely twice: after medical evaluation of clinical features (clinical gestalt [CG]) and after evaluation of clinical features and results of lung ultrasound or chest x‐ray (clinical and bedside imaging–integrated gestalt [CBIIG]). The final diagnosis was adjudicated after independent review of 30‐day follow‐up data. Results: Among 838 ED enrolled patients, 193 (23%) were finally diagnosed with COVID‐19. The area under the curve (AUC), sensitivity, and specificity of CG and CBIIG for COVID‐19 were 80.8% and 91.6% (p < 0.01), 82.9% and 91.4% (p = 0.01), and 78.6% and 91.8% (p < 0.01), respectively. CBIIG had similar AUC and sensitivity to reverse transcription–polymerase chain reaction (RT‐PCR) for SARS‐CoV‐2 on the first nasopharyngeal swab per se (93.5%, p = 0.24; and 87%, p = 0.17, respectively). CBIIG plus RT‐PCR had a sensitivity of 98.4% for COVID‐19 (p < 0.01 vs. RT‐PCR alone) compared to 95.9% for CG plus RT‐PCR (p = 0.05). Conclusions: In suspected COVID‐19, CG and CBIIG have fair diagnostic accuracy, in line with physicians' gestalt for other acute conditions. Negative RT‐PCR plus low probability based on CBIIG can rule out COVID‐19 with a relatively low number of false‐negative cases.